Financial Deepening and Stock Market Development in Nigeria: Evidence from Recent Data (1981-2019): Array - Tiamiyu, Kehinde A. (Acta Universitatis Danubius. Œconomica, 2022)
This study has so far investigated the link between financial deepening and the development of the stock market over the period of 1981 and 2019 using Bound test conintegration ARDL approach on the ground that Nigeria's financial sector is still shallow and lacks the necessary liquidity and capital to bring about the required development of stock markets in Nigeria. The Bounds cointegration test revealed that cointegration existed among the variables under investigation. As a result, both the short and long term models were empirically examined. In the long run, the significant drivers of stock market development in Nigeria are financial development, domestic saving as a ratio of GDP, broad money diversification and GDP as they are all significant determinants in term of signs, magnitude and size. This result parallels the findings of Okeya and Dare (2019). However, from 1981 to 2019, a considerable inverse relationship was seen between broad money diversification and stock market performance, contrary to projections. By implication, Nigerian financial sector lacks financial diversification in the long run. However, the finding supports the popular consensus that money is neutral in the long run as stock market mirrors economic condition of the country it represents. Nonetheless, the short run counterpart of the regression model showed that stock market development follows adaptive expectation in Nigeria as its previous values significantly determined the present values. However, unlike in the long run, financial development indicator exerts negative influence to stock market and but only becomes significant after some lags. This therefore reinforces the reality that private sectors lacks enough liquidity, limiting its beneficial contribution to the development of the stock market in the near term. This, by inference, confirms the shallowness of the Nigerian financial sector, as it lacks sufficient liquidity in the short run. Besides, regardless of model considered be it long run or short run, total domestic saving ratio of GDP has been a good candidate driving stock market development in Nigeria. Based on this conclusion, the Central Bank of Nigeria (CBN) is enjoined to liberate interest rate so as to allow for more robust operations of financial sectors in Nigeria.